Naruszenia praw człowieka w Polsce - perspektywa białoruska - Lesyk, Yulia (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2016)
The article describes violations of human rights in Poland as seen by the Ministry of Foreign Affairs of the Republic of Belarus. Two ministry reports have been drawn since 2013, con-cerning the violations of human rights determined in universal regulations. The authors from Belarus focus only on the arraignment of western countries. This article is devoted to the de-scription of situation in Poland.
Keywords: raporty; Polska; prawa człowieka; polityka zagraniczna; Białoruś